2003
DOI: 10.1088/0954-3899/29/6/316
|View full text |Cite
|
Sign up to set email alerts
|

Search for large-scale coincidences in network observation of cosmic ray air showers

Abstract: The Large Area Air Shower (LAAS) group has been performing a network observation of extensive air showers (EAS) since 1996 in Japan. Eight compact EAS arrays (ten in the near future) are operating simultaneously and independently at distant stations (up to ≈ 1000 km), constituting a gigantic detector system as a whole. Using five stations' datasets, large-scale coincidences of EAS have been searched for with the aim of detecting signals from extremely short bursts in the universe. By comparing arrival times an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…We know of no previous cosmic ray experiment that would be sensitive to correlated shower events at these energies separated by 10-50 km. The LAAS experiment [9] has only eight sites at much larger distances (∼500 km) and would have seen <1 event given the rate we observe (assuming the correlations persist to those larger distance scales).…”
Section: Discussionmentioning
confidence: 66%
“…We know of no previous cosmic ray experiment that would be sensitive to correlated shower events at these energies separated by 10-50 km. The LAAS experiment [9] has only eight sites at much larger distances (∼500 km) and would have seen <1 event given the rate we observe (assuming the correlations persist to those larger distance scales).…”
Section: Discussionmentioning
confidence: 66%
“…It covers local detection networks in Canada and the USA (ALTA, SALTA (SAL), WALTA (WAL), CHICOS (CHI), CROP (CRO), etc.). A similar project is running in Japan (LAAS (Ochi et al, 2003)) and detection stations are being built on the roofs of European high schools, too -in Sweden (SEASA (SEA)), Germany (SkyView (Sky)), the Netherlands (HiSPARC (HiS)), Great Britain (Cosmic School (Cos)) among other countries.…”
Section: Czeltamentioning
confidence: 99%
“…In 1994 Swiss group (Carrel and Martin, 1994) reported an interesting temporal increase of distant time-correlated showers. LAAS group (Ochi et al, 2003) reported few interesting candidates of correlated showers on large distance. However, interpretation that these events were only accidentally correlated, is also plausible.…”
Section: Very Large Area Coincidencesmentioning
confidence: 99%
“…The Large Area Air Shower (LAAS) experiments [1,2] have been observing cosmic rays with compact Extensive Air Shower (EAS) arrays, and have maintained EAS arrays at several institutes since 1996. The purposes of LAAS experiments are to study the primary energy spectrum, anisotropy of high energy cosmic rays, and simultaneous and parallel EAS events [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%